Organization of War Prisoners Security and Prevention of Escapes in the Camps of the People’s Commissariat for Internal Affairs and the Ministry of Internal Affairs of the USSR in 1941-1956 - Sidorov Sergey Grigoryevich (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2015)
The organization of guarding the prisoners of war in the People’s Commissariat for Internal Affairs (NKVD) and in the Ministry of Internal Affairs (MVD) camps of the USSR in the war and post-war years underwent essential changes. If at the beginning of the war the convoy troops escort was allocated on guarding the soldiers of the enemy at the rate of 1 convoy for 8 prisoners of war, in 1943 it was impossible to allocate escort at this rate because of the mass arrival of prisoners of war in People’s Commissariat for Internal Affairs camps. Escort number for guarding the contingent at works was determined at the rate of 1 convoy for 15 prisoners of war, in 1944 – already for 25 prisoners. The insufficient organization of guarding, proximity of a front line, strong belief of the German soldiers in a victory of Wehrmacht led to escapes. In 1943 the share of prisoners of war that made escape was the highest during all years of prisoners staying in the USSR and made 0,4% of their total number in the NKVD camps in the end of the year. In 1945 over 100 new camps for the prisoners of war consisting of more than 1600 camp subdivisions were organized in the USSR. During this organizational period the share of the prisoners of war who made escape grew a little. However, almost all escapes were unsuccessful. In 1946 only 29 escaped prisoners out of 5761 weren’t caught. During the post-war period the auxiliary teams formed of the prisoners of war started playing the increasing value for guarding the camps. The number of the convoy troops was annually reduced. Help to the management of camps in 1947 in a capture of the escaped prisoners of war was given by crews of tens of thousands of people from the local population. In the conditions of reducing the convoy troops the regime camp and camp offices for the prisoners who made earlier escape with the strengthened guard were created to prevent the growth of escapes. In 1949 in the not-regime camps the teams of self-guarding consisted of the checked prisoners of war (anti-fascists) were entered. The created system of guarding the NKVD-MVD camps was reliable. In 1943-1948 only 350 prisoners of war out of 11403 who made escape were not caught.